Meshfree approach for linear and nonlinear analysis of sandwich plates: A critical review of twenty plate theories. (August 2016) - Solanki, Manoj Kumar; Mishra, Sabin Kumar; Singh, Jeeoot
Abstract: Present paper reviews twenty different theories used for analysis of multilayered plates. The mathematical formulation of the actual physical problem of the plate subjected to mechanical loading is presented using von Karman nonlinear kinematics. These non-linear governing differential equations of equilibrium are linearized using quadratic extrapolation technique. A meshfree approach based on polynomial radial basis function is used for obtaining the solution. The results obtained for the sandwich plate are validated with other available results. It is observed that some theories under predicts the deflection by a reasonable amount. The effect varying core thickness on stresses and deflection of the sandwich plate is also presented.